EARLY COMPLICATIONS AFTER SECONDARY BREAST RECONSTRUCTION USING LATISSIMUS DORSI MYOCUTANEOUS FLAP AND SILICONE BREAST IMPLANTS - Milan Ranisavljevic; Ljiljana Budisic Ranisavljevic; Vladimir Selakovic; Dejan Lukic (Sanamed, 2020)
Introduction: Secondary breast reconstruction is a multifactorial decision. It is based on the need for neoadjuvant/adjuvant treatment, lifestyle and expected cosmetic outcome of the patient. Aim of this study was to show early complications related with secondary breast reconstruction using latissimus dorsi miocutaneous flap and silicone breast implants.